The Influence of Long-Term and Short-Term Institutional Investors on Complicated Mispricing of Stocks. (10th November 2020) - Liu, Bing
Abstract : Taking Chinese listed companies from 2009 to 2017 as the research objects, this paper aims at exploring the heterogeneous effect of short-term and long-term institutional investors on stock mispricing. The empirical study finds that long-term institutional investors have an inhibiting effect on stock mispricing, while short-term institutional investors have an opposite effect. When the company information opacity is high, long-term institutional investors have a more obvious inhibiting effect on stock mispricing while short-term institutional investors have a more obvious promoting effect on stock mispricing. When the attention of analysts is enhanced, long-term institutional investors further restrain the stock mispricing while short-term institutional investors further promote the stock mispricing.